1989
DOI: 10.1002/1097-0142(19890201)63:3<484::aid-cncr2820630316>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of urinary neopterin in non-Hodgkin's lymphomas

Abstract: Neopterin excretion levels were assessed in 66 consecutive patients affected by non-Hodgkin's lymphomas (NHL). The logarithm of the mean value of the whole series was 2.71 (log [mumol neopterin/mol creatinine]), significantly higher (P less than 0.001) than the control value (2.12). Fifty-six of 66 patients had a raised excretion of neopterin in amounts statistically related to the stage of disease. The mean value (2.51) of patients in Stages I-II was lower than the mean value (2.86) of patients in Stage III-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Thus, neopterin as an indicator of activation of cell-mediated immune mechanism differs from a selection of several routine laboratory variables which carry practically no predictive information. This major result of the present study on lung cancer patients agrees with analogous observations in other malignancies: neopterin was found to be a significant and independent predictor in carcinoma of the uterine cervix (11) or of the ovaries (12), in prostatic carcinoma (13), in patients with hepatocellular carcinoma (14), in various haematological neoplasms (15)(16)(17), and in colon carcinoma (18).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, neopterin as an indicator of activation of cell-mediated immune mechanism differs from a selection of several routine laboratory variables which carry practically no predictive information. This major result of the present study on lung cancer patients agrees with analogous observations in other malignancies: neopterin was found to be a significant and independent predictor in carcinoma of the uterine cervix (11) or of the ovaries (12), in prostatic carcinoma (13), in patients with hepatocellular carcinoma (14), in various haematological neoplasms (15)(16)(17), and in colon carcinoma (18).…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that neopterin levels increase in body fluids and change in parallel to the activity of the disease in many infectious diseases and various malign disorders in which activation of the cellular immune system plays an important role in the pathogenesis [7,16,17] . It has been shown that the activation of cellular immune system stimulates the secretion of γ-interferon from the T lymphocytes, and γ-interferon is an effective inducer of neopterin release by monocytes/macrophages [10] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that there is a relation between neopterin levels in biological materials, the changes in their elimination rates and various pathological conditions. In addition to its association with activation of cell-mediated immunity and with cell expansion, significant changes were seen in neopterin levels and elimination rates in viral diseases (for example viral hepatitis) [2,3] , atypical phenylketonuria [4] , organ and tissue rejection [5] , autoimmune diseases (such as rheumatoid arthritis and systemic lupus erythematosus [6] ), genital cancer and hematologic neoplastic disorders [7,8] . In all these cases, enhanced concentrations of neopterin have been shown to have prognostic significance [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Thi s effect can be sy nergisticall y enhanced by tumor necrosis factor alpha (6). Neopterin has been shown to be of prognostic value in Hodgkin's disease, nonHodgkin's lymphoma and chronic myelogenous leukemia (7,8).…”
Section: Introductionmentioning
confidence: 99%